P09235-AMINOLEVULINIC ACID PREVENTS LIPID-INDUCED ER STRESS AND APOPTOSIS BY INDUCING HEME OXYGENASE-1. (6th June 2020) - Mae, Yukari; Kobayashi, Yui; Takata, Tomoaki; Hosokawa, Kohshiro; Sugihara, Takaaki; Kanda, Tsutomu; Isomoto, Hajime
Abstract: Background and Aims: A growing number of evidence indicates the association with dyslipidemia and the progression of chronic kidney disease. Endoplasmic reticulum (ER) stress and apoptosis in renal tubule are suggested to be linked to the pathophysiology of toxic lipid-induced kidney injury. 5-aminolevulinic acid (ALA) is a precursor of heme oxygenase (HO)-1, which plays an important role in protecting cells from various stresses. In the present study, we aimed to investigate the therapeutic effect of ALA, on toxic lipid-induced ER stress and apoptosis in the renal tubule. Method: Renal proximal tubular epithelial cells (RPTECs) were treated with palmitic acid to induce ER stress and apoptosis. ALA was also added with palmitic acid (PA). The gene and protein expressions of NF E2-related factor 2, HO-1, glucose-regulated protein (GRP)78, and C/EBP-homologous protein (CHOP) were quantified. Apoptotic cells were evaluated by caspase-3/7 assay. An HO-1 inhibitor, Zn-protoporphyrin IX, was added to investigate the involvement of HO-1 in ALA-mediated therapeutic effect on the ER stress and apoptosis. Results: The expressions of GRP78 and CHOP increased in cells treated with PA. Apoptotic signals also increased with PA treatment. ALA induced a significant increase in the HO-1 expression and that led to the suppression of ER stress response. Apoptotic signals in PA-treated cells also decreased with ALA and the effect of ALA disappeared when combined with Zn-protoporphyrin IX. Conclusion: PA-induced ER stress and apoptosis in RPTECs. ALA has a therapeutic effect by suppressing ER stress, possibly through HO-1 induction.